Modelling of chemical wear relevance to practice - Sethuramiah, A. (Elsevier, 2016)
Bridging the gap between theory and practice, this guide is a one-stop resource for students, researchers, and professionals seeking quick and effective tribological evaluations of environmentally friendly and energy efficient products. -- Edited summary from book.